2020
DOI: 10.2967/jnumed.120.246595
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Evaluation of CD20 Expression Using 64Cu-Labeled F(ab′)2 Fragments of Obinutuzumab in Lymphoma

Abstract: CD20-overexpressed non-Hodgkin lymphoma typically indicates progressive malignancy. Obinutuzumab is a next-generation Food and Drug Administration-approved humanized monoclonal antibody that targets CD20. Previous studies with 89 Zr-labeled obinutuzumab have successfully imaged CD20 in vivo. However, delayed tumor uptake and increased radioactive exposure caused by long blood circulation limit its clinical translation. This study aimed to develop 64 Cu-labeled F(ab′) 2 fragments of obinutuzumab for imaging CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…[ 12 ] CD38 has been found to be highly expressed for some lymphoma such as MM. [ 25 ] The first anti‐CD38‐humanized mAb daratumumab was subsequently approved for the treatment of relapsed MM. In our study, 89 Zr‐labeled dara showed a high tumor uptake at around 20 %ID g −1 and low uptake in other nontarget organs for CD38‐positive models, providing excellent tumor contrast.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 12 ] CD38 has been found to be highly expressed for some lymphoma such as MM. [ 25 ] The first anti‐CD38‐humanized mAb daratumumab was subsequently approved for the treatment of relapsed MM. In our study, 89 Zr‐labeled dara showed a high tumor uptake at around 20 %ID g −1 and low uptake in other nontarget organs for CD38‐positive models, providing excellent tumor contrast.…”
Section: Discussionmentioning
confidence: 99%
“…Its stability was analyzed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and radio thin-layer chromatography (TLC) analysis as previously reported. [25] PET Imaging of 89 Zr-Labeled Antibodies: PET imaging was performed using an Inveon PET/CT scanner (Siemens) after intravenously injecting 89 Zr-labeled dara (≈7.4 MBq). At each time point, mice were anesthetized and scanned in a prone position.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, passive tracer excretion via the kidneys may hinder active observation of renal dysfunction, scaling down necessary imaging contrast needed for confident diagnosis. Low molecular weight antibody fragments in the forms of Fab, single-chain Fv fragment (scFv), diabody, and nanobody, have all been found to excrete from the kidneys 1 , 13 . Going through lysosomal proteolysis, glomerular filtration, and subsequent tubular reabsorption, these radioactive renal metabolites display rapid renal excretion and steady kidney retention, adding difficulties to kidney function interpretation.…”
mentioning
confidence: 99%